Correlation Between Hormonal Contraceptives Use and Age of Menarche with Breast Cancer Among Women in Indonesia: A Systematic Review - Ermi, N; Kamso, S (KnE Life Sciences, 2019)
Cancer is one of the leading causes of death worldwide. According to GLOBOCAN, International Agency for Research on Cancer 2012, it is known that breast cancer is cancer with the highest percentage of new cases, at 43.3%, and percentage death due to breast cancer by 12.9%. Although the incidence of breast cancer in Asia remains lower than in North America, Western Europe, and Oceania, the rates have been increasing rapidly during the past few decades, and Asian countries now account for 40% of breast cancer cases diagnosed worldwide. Southeast Asian countries have moderate rates for breast cancer, with a higher incidence of one in Indonesia. Breast cancer morbidity and mortality increased among Indonesian women. These increased rateswere associated with higher prevalence of breast cancer risk factors such as hormonal contraceptive use and age of menarche. The purpose of this study was to determine the correlation between hormonal contraceptives use and generation of menarche with breast cancer among women in Indonesia. This study used a systematic review made by PRISMA. Searching for literature sources through online databases such as Science Direct, JSTOR, and Proquest, additional records identified through Google Scholar by using relevant keywords adjusted by inclusion and exclusion criteria. Five studies included in this review. All studies discussed breast cancer among women in several regions in Indonesia. There was a significant correlation between hormonal contraceptives use and age of menarche with breast cancer among women in Indonesia. Women may be more careful in determining the duration of hormonal contraceptive use and avoiding a lifestyle that can accelerate menarche. Keywords: Hormonal contraception, Age of menarche, Breast cancer, Indonesia